Can PPSV-23 Vaccine Impact Exacerbations of Chronic Cough Symptoms and Medication Use in Younger Adult Asthmatics? A Clinical Question That Needs Answering - Alessandra M. Lanz; Esther Chartrand; Claudia P. Eisenlohr; Miguel J. Lanz (Vaccines, 2022)
Symptoms of chronic cough (CC) from the airways are commonly treated with antibiotics, antitussives, bronchodilators, and steroids. There is a wide variability in treatment response, dependent on the exact cough etiology. Our case-series study was composed of 71 nonsmoking adults, 59 females, mean age 43 (±21) years, with a history of CC-asthma and history of ≥2 exacerbations/year requiring systemic steroids and/or antibiotics. All had decreased Streptococcus pneumoniae antibody titers, with a mean average of 3 of 23 normal serotypes and were subsequently vaccinated with PPSV-23. Pre- and post-12-month vaccination questionnaires were administered, and 35 (54%) reported both decreased CC symptoms and asthma medication use. Baseline comparisons to those with no change in CC symptoms or asthma medication use revealed significantly lower exhaled nitric oxide (FeNO) levels (17 ± 10; 62 + 40 ppb), serum eosinophils (192 ± 156; 280 ± 166/mcL), and total IgE (132 ± 167; 275 ± 290 IU/mL) in those with improvement post-vaccination. Higher baseline symptoms scores for upper respiratory infections as a trigger to their CC (* p > 0.05) were found in those responding to PPSV-23. These data reveal a subset of asthma in younger adults, <65 years, with significantly decreased S. pneumoniae antibody titers with less CC symptoms and asthma medication use for exacerbations after PPSV-23 vaccination.